Final Report : Peer Review in Online and Blended Learning Environments. - McKenzie, Jo; Parker, Nicola (Australian Learning and Teaching Council (ALTC), 2011)
Final report from a project that sought to develop, implement and evaluate a scholarly framework, processes and resources for peer review of learning and teaching in online and blended learning environments. Specific issues relating to online and blended learning environments were identified as well as the need for formative feedback and professional development. Workshop materials, case studies, and an annotated bibliography are among the resources on the project website. The project aimed to address the issues of how to develop, define, assess and provide feedback on graduate attributes for business students effectively, in a way that is educationally meaningful, professionally relevant and measurable. During the implementation of the project, educators and students were provided with access to online systems and support to facilitate a transparent, reliable and criterion-referenced learning environment for the attainment of the designated graduate attributes with opportunities for reflection and review.